Emotional Intelligence as Predictor to Burnout Syndrome Among Teachers in Delta State - Benson, Blessing Owere; Ekechukwu, Rosemary O (Advances in Social Sciences Research Journal, 2023)
The study was conducted using a correlational research design. A total of 752 teachers in the 20 government-owned senior secondary schools in Delta State’s Ika South Local Government Area were included in the study (Source: Post Primary Education Schools Board, Asaba, Delta State, 2021). The study used a sample size of 398 teachers who were chosen at random and independently from 20 government-owned secondary schools in the Ika South Local Government Area of Delta State, Nigeria, using the purposive sampling technique. The purposive sample technique is appropriate for selecting teachers who exhibit the traits that are being examined, namely, Burnout Syndrome. This was accomplished by giving each teacher a copy of the Burnout Syndrome Screening Scale (BSSS). Data was collected using the Emotional intelligence inventory (El) by Akinboye (2005), and Maslach Burnout Scale (MBS). The Cronbach alpha method of internal consistency was used to assess the instruments’ dependability. The reliability coefficients were Maslach Burnout Scale (MBS) 0.87, and Emotional Intelligence Inventory (El) 0.79, which are high enough to demonstrate the instrument’s reliability. Linear regression and multiple regression were used to evaluate the hypotheses, along with independent sample t-test statistics. The result revealed that emotional intelligence such as self-awareness, self-management, self- motivation, social awareness, and relationship management all predict teacher burnout syndrome in a favorable and substantial way. School boards should recruit more professional counsellors to reduce post-traumatic stress disorder (PTSD) among teachers.